New insights on the Permian and Triassic vertebrates from the Iberian Peninsula with emphasis on the Pyrenean and Catalonian basins - Fortuny, J.; Bolet, A.; Sellés, A.G.; Cartanyà, J.; Galobart, À. (Journal of Iberian Geology, 2011)
Few studies paid attention to the Permian and Triassic vertebrates from the Iberian Peninsula and a re-evaluation of these faunas is needed in order to compare them with other European basins. As a first step, we present here the available data from the Catalonian and Pyrenean basins (NE of the Iberian Peninsula), offering new insights on the diversity and temporal distribution of their vertebrate faunas. The two basins have yielded unexpectedly abundant and diverse vertebrate assemblages, including fishes, amphibians and reptiles from continental and marine environments. The revision of classical finds and the analysis of new material provide data towards an understanding of the evolutionary and palaebiogeographical history of the Permian and Triassic vertebrate Iberian faunas. Permian remains mainly correspond to footprints recovered from alluvial deposits; the osteological record is scarce in the Iberian Peninsula. Early Triassic vertebrate localities are unknown. Middle Triassic faunas are abundant and reflect the change from continental environments to a wide diversity of coastal and marine depositional environments. During the Anisian, faunas are represented by footprints and skeletal remains of amphibians (capitosaurs) and terrestrial reptiles (archosauromorphs and procolophonoids). Ichthyofauna, sauropterygians, thalattosaurs and protorosaurians are known through the late Anisian and Ladinian. Finally, Late Triassic localities representing coastal environments have also yielded marine reptiles (sauropterygians) and a diverse ichthyofauna.